The Effectiveness of Pelvic Rocking Exercises (PRE) Movement with Birthing Ball on ?-Endorphin Levels in III Trimester Pregnant Women - Eni Lestari (Alta Dharma Publisher, 2020)
One of the discomforts in pregnancy is back pain and it will increase along with the increasing of gestational age. Pelvic rocking exercises using birth balls can stretch pelvic muscles, manage pain and increase comfort, thereby they can relax the body and increase beta endorphin levels. The study aimed to analyze the differences of pelvic rocking exercises of right-to-left, back-forward and rotating movements using a birth ball against beta-endorphin levels. This study used a quasi-experimental method with a pre-posttest design. The sampling technique used accidental sampling with a total sample of 30 samples. Respondents were divided into 3 groups using a simple random method, group 1 was given the right-to-left pelvic rocking exercises, group 2 was given the back-forward pelvic rocking exercises and group 3 was given the rotating pelvic rocking exercises using a birth ball with duration of 30 minutes for 8 meetings. Analysis using paired tests, one-way test and covariance analysis test with a value: 5%. There was no difference in pelvic rocking exercises of right-to-left, back-forward and rotating movements using the birth ball to ?-endorphin levels. Pelvic rocking exercises of right-to-left, back-forward and rotating movements using a birth ball could not increase beta endorphin levels in pregnant women.